Pathological complete response after nivolumab therapy following angiogenesis inhibitors in a patient with metastatic renal cell carcinoma - Hagimoto, Hiroki (IJU Case Rep, 2020)
INTRODUCTION: Nivolumab is effective for advanced renal cell carcinoma; however, reports are limited wherein nivolumab is combined with sequential therapy of angiogenesis inhibitors and metastasectomy. CASE PRESENTATION: A 65‐year‐old man was diagnosed with left renal cell carcinoma of cT2aN0M1 with lung metastasis. The patient underwent nephrectomy and sequential therapy with interferon‐α and angiogenesis inhibitors. Lung metastasis decreased by angiogenesis inhibitors, but new right adrenal gland metastasis appeared. Nivolumab as the fifth systemic therapy remarkably shrank the metastasis. After discontinuing nivolumab therapy, the metastasis continued to shrink. The patient underwent adrenalectomy, and pathological analysis revealed no remnant cancer cells in the specimen, confirming a pathological complete response. Twenty months postoperatively, he remains in good health without recurrence. CONCLUSION: We report a rare case with renal cell carcinoma of a pathological complete response by nivolumab after angiogenesis inhibitors.